High frequency of rapid immunological progression in African infants infected in the era of perinatal HIV prophylaxis. - Mphatswe, W; Blanckenberg, N; Tudor-Williams, G; Prendergast, A; Thobakgale, C; Mkhwanazi, N; McCarthy, N; Walker, B; Kiepiela, P; Goulder, P (2007)
OBJECTIVES: To determine the natural history of HIV infection following peripartum single-dose nevirapine (sd-NVP) prophylaxis in a resource-limited country, and to assess implications for antiretroviral therapy (ART) roll-out programmes. METHODS: Infants of HIV-infected mothers in KwaZulu-Natal, South Africa, were tested on days 1 and 28 to detect intrauterine (IU) and intrapartum (IP) infection. Infant follow-up included monthly viral load and CD4 cell measurement. ART was initiated at infant CD4 cell% < or = 20%. RESULTS: In 740 infants born to 719 HIV-infected women, mother-to-child transmission (MTCT) was 10.3% (69% IU, 31% IP). Median viral load was higher in mothers of infants infected IP than IU (279 000 versus 86 600 copies/ml; P = 0.039) and lower in mothers of uninfected infants (median 26 750 copies/ml; P < 0.001). Peak viraemia was higher in infants infected IP than IU (5 160 000 versus 984 000 copies/ml; P < 0.001). Median viral load at birth in IU-infected infants (155 000 copies/ml) fell 1.4 log to 6510 copies/ml by day 5 and was beneath the detection limit using dried blood spot analysis in 38% of infants. CD4 cell% declined rapidly, to < or = 20% in 70% and < or = 25% in 85% [current World Health Organization (WHO) criteria for initiating ART] of infants by 6 months. CONCLUSIONS: MTCT was reduced by sd-NVP through an effect on IP transmission. Where MTCT occurred despite NVP, two-thirds of transmissions arose IU; IP-infected babies were born to mothers with very high viral load. Disease progression was particularly rapid, 85% infants meeting WHO criteria for ART within 6 months. These findings argue for more effective MTCT-prevention programmes in resource-limited countries.